Dynamics of Hubbard Nano‐Clusters Following Strong Excitation. Issue 10 (December 2013) - Bonitz, M.; Hermanns, S.; Balzer, K.
Abstract The Hubbard model is a prototype for strongly correlated electrons in condensed matter, for molecules and fermions or bosons in optical lattices. While the equilibrium properties of these systems have been studied in detail, the excitation and relaxation dynamics following a perturbation of the system are only poorly explored. Here, we present results for the dynamics of electrons following nonlinear strong excitation that are based on a nonequilibrium Green functions approach. We focus on small systems—"Hubbard nano‐clusters"—that contain just a few particles where, in addition to the correlation effects, finite size effects and spatial inhomegeneity can be studied systematically. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)